1988
DOI: 10.3109/00365528809099146
|View full text |Cite
|
Sign up to set email alerts
|

Peptic Ulcer Disease in the Elderly

Abstract: Gilinsky NH. Peptic ulcer disease in the elderly. Scand J Gastroenterol 1988, 23 The elderly are a growing minority; they comprise approximately 12% of the population hut consume an increasing proportion of health care resources. Disease in the aged is unique in many ways, demanding special attention and study. This is particularly evident with regard to peptic ulceration, which is a more serious disorder in the elderly than in younger individuals, often presenting in an atypical manner and having a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The rate of perforated peptic ulcers has tended to decrease [4,6,8,9]. Concomitantly, a gradual relative increase in elderly persons sustaining a perforation has been observed [4,6,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of perforated peptic ulcers has tended to decrease [4,6,8,9]. Concomitantly, a gradual relative increase in elderly persons sustaining a perforation has been observed [4,6,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…These pathophys iological considerations are indirectly con firmed by the excellent clinical results [11,[26][27][28] obtained in the elderly with antisecretory drugs. 258 Pilotto/Viancllo/Di Mario/Plebani/ Farinati/Azzini…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest an increased susceptibility of the gastric mucosa to damage in the elderly. However, it is also interesting to consider gastroduodenal secretory capacity in peptic ulcer patients in relation to advanc ing age; in fact, it is important to know wheth er there is a different acid and/or pepsin out put corresponding to the epidemiological and clinical differences in ulcer disease in the elderly, who suffer a higher morbidity and mortality [11]. The aim of this retrospective study was therefore to evaluate the influence of age on gastric acid and pepsin secretion in a large sample of GU and DU patients.…”
Section: Introductionmentioning
confidence: 99%
“…bleeding and perforation, are more frequent in the elderly [2,3]. Recently, studies have demonstrated that the recurrence of both GU and DU is markedly decreased after the cure of HP infection [4][5][6][7][8]; however, until now, no data has been published regarding the clinical outcome of HP-associated GU and DU in elderly people treated for HP infection.…”
Section: Introductionmentioning
confidence: 90%